2008
DOI: 10.1177/147323000803600304
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Oral Clodronate Compared with Oral Ibandronate, Intravenous Zoledronate or Intravenous Pamidronate in Breast Cancer Patients

Abstract: This study aimed to identify the effects of different bisphosphonates in reducing skeletal-related events, and to determine whether there are any differences in their cost-effectiveness, taking into account their efficacy, safety profile and administration routes. A systematic literature search of databases, such as PubMed and the Cochrane Controlled Trials Register, supplemented by the latest congress abstracts from meetings of the European Hematology Association and the American Society of Clinical Oncology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…However, in analyses that rely on clinical trial data to estimate cost-effectiveness [26,28,29], the applicability to the real-world setting may be confounded by factors such as higher-than-normal rates of persistence with therapy (in the case of oral BPs).…”
Section: Discussionmentioning
confidence: 98%
“…However, in analyses that rely on clinical trial data to estimate cost-effectiveness [26,28,29], the applicability to the real-world setting may be confounded by factors such as higher-than-normal rates of persistence with therapy (in the case of oral BPs).…”
Section: Discussionmentioning
confidence: 98%
“…Even though some economic analyses regarding breast cancer exist [15], [16], [17], breast cancer attributable costs have not yet been reported for Germany. The objective of this study is to estimate breast cancer attributable health expenditures for Germany.…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacoeconomic implications of each drug vary based on factors such as dosage, spacing of hospital visits, and route of administration. In a 2008 study, researchers created a costeffectiveness analysis using Germany and United Kingdom (UK) health data to compare oral clodronate, oral ibandronate, IV zoledronate, and IV pamidronate as adjuvant treatments, alongside chemotherapy, for metastatic breast cancer [88]. Considering the frequency of hospital visits, drug acquisition costs, cost of transportation, the likelihood of adverse events based on BP, and improvement of quality of life, researchers found that in both countries, oral clodronate had the lowest cost per patient, followed by oral ibandronate.…”
Section: Cost Effectivenessmentioning
confidence: 99%